Strengthening mathematical translation through project and problem-based instruction in primary schools - Purwanti Purwanti; H. Sujati (Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the comparative impact of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) on elementary school students' ability to transform word problems into mathematical sentences. The research addresses a critical issue in mathematics education where students often struggle to interpret contextual story problems, which hinders their problem-solving skills. Utilising a quasi-experimental design, the study involved 32 fifth-grade students randomly selected from a population of 56 at SD Negeri Kauman Pleret. Participants were divided equally into control and experimental groups, receiving instruction through the PBL and PjBL models, respectively. Data were collected through written tests and classroom observations, with the validity of assumptions tested via normality and homogeneity checks. An independent samples t-test was used to analyse differences in learning outcomes. The findings reveal that the PjBL model significantly outperformed the PBL model in enhancing students’ abilities, with the PjBL group achieving a higher post-test mean score (M = 12.06) compared to the PBL group (M = 9.69). The significance value (p = 0.011) confirms the statistical difference between the two instructional approaches. These results suggest that PjBL is a more effective model for fostering mathematical comprehension through contextual problem-solving tasks, highlighting its potential for broader application in mathematics instruction.